Identification of drug-related problems during pharmaceutical care services - introduction to the Geriatric Department at the Universit - Baralić Knezevic, Ivana; Arsenovic, Branka; Stefanovic, Katarina; Trifunovic-Balanovic, Dragana (General Practice, 2024)
Introduction: Patients with multiple comorbidities and undergoing polypharmacy are at a high risk of experiencing drug-related problems (DRPs). These DRPs can lead to increased morbidity, mortality, and healthcare costs. Objective: This study aims to identify the prevalence and causes of DRPs in geriatric inpatients, as well as the factors that contribute to them. Additionally, the study intends to evaluate the implementation of ward-based pharmacy services in the geriatric department. Method: The pharmacist analyzed inpatient therapy, identified DRPs, and formulated recommendations. DRPs were categorized according to the PCNE-DRP classification, version 9. A total of 100 patients, of which 52% were men, average age of 79.7±7.88 years, were included in the study. Results: Our study found that on average, each patient had 2.36 drug-related problems (DRPs). The most common DRP was related to treatment safety, accounting for 44.9% of cases, followed by treatment effectiveness (33.1%) and unnecessary drug treatment (22%). The main cause of DRPs was inadequate drug selection (61%) and inadequate dose selection (38.1%). Patients with atrial fibrillation and chronic renal failure had more DRPs than those without these conditions. In total, we identified 229 interventions to address these DRPs. However, the acceptance rate of these recommended interventions was low at 25.9%. Conclusion: The rate of drug-related issues in elderly hospital patients was found to be high, but the rate of acceptance of interventions to address these issues was low. In order to enhance the implementation of pharmaceutical services and improve healthcare for elderly patients, it is crucial to improve the collaboration between healthcare providers and pharmacists. Recognizing the unique skills and expertise that pharmacists bring to the table can facilitate their integration as a valuable member of a multidisciplinary healthcare team